Model for business-it alignment: A case of Malaysian public universities - Esmadi Abu Abu Sema; Tamrin Amboala; Iza Azura Ahmad Bahar; Hamid, N.A.A.; Al-Qdah, M.S. (Little Lion Scientific, 2020)
Business and Information Technology (IT) alignment is defined as applying IT in an appropriate and timely way, in harmony with business strategies, goals and needs. One important issue in business-IT alignment study is the absence of alignment. Findings indicate that there are many factors/variables that consistently enhance business-IT alignment. By identifying factors to achieve business-IT alignment, the problem on the absence of alignment could be addressed. Due to the complexity of business-IT alignment, there is possibility that successful alignment focuses on managing specific alignment dimension by investigating factors that encourage particular dimension. Literature on alignment discovered that there seems to be confusion in clarifying the business-IT alignment concept. Based on this gap, this research examined problem, issues on alignment, identified, analyzed, and discussed factors affecting alignment, then categorized the constructs identified into dimensions and proposed a model on factors influencing alignment in universities. The model developed is based on Resource Based View, Knowledge Based View, Uncertainty Reduction and Contingency theory and business-IT alignment models which were developed in prior studies in order to examine the influence of strategic, structural, social and cultural on business-IT alignment in public universities in Malaysia. 18 hypotheses have been developed framed on three research questions. The data for analysis was collected via a structured questionnaire survey that yielded 148 usable questionnaires from IT managers/executives and top administrators in 20 public universities who are involved in IT strategic planning. Data were analyzed using SPSS for descriptive and demographic analysis, while the model that was developed was validated using Structural Equation Modeling analysis (SEM). The result of the goodness of fit index satisfies the recommended value while 18 hypotheses were supported. The validation of results revealed that the entire model fit is appropriate and indicated the stability of the theory used in building the Business IT alignment model. The findings showed business-IT alignment is significantly affected by the four sets of factors: strategic, structural, social and cultural. Findings from this study provide insights to enable university's top administrators to develop more comprehensive action plans for achieving greater business-IT strategic alignment, and for translating alignment into enhanced IT effects on university's performance.